Financiamento ao comércio internacional de commodities: financiamento às exportações brasileiras sob modalidade de recebimento antecipado de exportação - Slav, Heloisa Gomes (2015)
The purpose of this work is to analyze legal issues related to the international trade finance of commodities with a particular focus on pre-export finance. In light of the importance of this transaction, which is sanctioned by the monetary authorities as an 'Advanced Payment for Exports,' to promoting Brazilian exports, the author seeks to analyze legal instruments established under Brazilian legislation or socially typified, which are premised on the implementation of contractual and collateral structures aimed at eliminating basic risks in cross-border transactions with emerging economies such as Brazil. These instruments are applied during the various stages of the structured trade and commodity finance, and pose challenges for their agents – financiers, executives, and attorneys – related to obligations, risks, liabilities, collaterals, and contingencies that are under-explored in the legal literature. The topic is examined in nine chapters. The first chapter reviews the various types of trade finance transactions; the second chapter analyzes structured trade and commodity finance transactions; the third chapter deals with the parameters of rationalities (such as combined analyses of balance sheets, cash flows and assets mobilization) adopted by foreign lenders in order to provide credit to exporters; the fourth chapter is reserved for a detailed study of the transaction’s risks and their mitigation; the fifth chapter discusses the key features of pre-export finance; the sixth chapter is dedicated to regulatory aspects, concept, features, and field of application of the 'Advanced Payment for Exports'; the seventh chapter analyzes contractual aspects that are inherent to a pre-export finance transaction; the eighth and ninth chapters are dedicated to a study of collaterals, particularly with respect to the preservation of goods and rights granted as collateral for the purpose of reimbursing the capital to the foreign lender. From this perspective, the key elements of structured finance for Brazilian commodities exports shall be analyzed in order to contribute to the improvement and dissemination of these business and legal mechanisms (that are still restricted to a highly specialized audience), which were designed to promote economic development in Brazil.